1992
DOI: 10.1159/000168423
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hypercalcemia on Renal Sympathetic Nervous System Activity

Abstract: Since calcium plays a modulatory role in the activity of the sympathetic nervous system (SNS), in these studies, we have tested the hypothesis that hypercalcemia may alter renal SNS activity, and, consequently, renal function. Acute hypercalcemia was induced in Sprague-Dawley rats by infusion of calcium 30mg/kg/2h in 0.45% saline. A control group of rats received only 0.45 % saline. Two more groups of rats received either calcium or 0.45 % saline 7-10 days after total renal denervation. Calcium infusion increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
1996
1996

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…There is no indication that mod erate changes in the level of calcium would affect this secretion. Moreover, in animal studies similar levels of calcium did not change GFR [5][6][7], while higher levels depressed it [8,9], In humans, no change [3], as well as slight elevation of GFR [6], have been reported. Although higher levels of calcium may cause hypertension [10], most authors also found no changes in blood pressure [1,2,5,11].…”
Section: Discussionmentioning
confidence: 92%
“…There is no indication that mod erate changes in the level of calcium would affect this secretion. Moreover, in animal studies similar levels of calcium did not change GFR [5][6][7], while higher levels depressed it [8,9], In humans, no change [3], as well as slight elevation of GFR [6], have been reported. Although higher levels of calcium may cause hypertension [10], most authors also found no changes in blood pressure [1,2,5,11].…”
Section: Discussionmentioning
confidence: 92%